1987
DOI: 10.1111/j.1550-7408.1987.tb03188.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, Morphology, and Locomotion of Paramoeba pemaquidensis Page (Amoebida, Paramoebidae): Effects of Substrate Charge Density and External Cations1

Abstract: Morphology and locomotive behavior in the marine amoeba, Paramoeba pemaquidensis Page, was examined under different environmental conditions. Paramoeba requires a minimum surface negative charge density for adhesion of amoebae to substrata. Once adhesion to the substratum has been attained, however, surface negative charge density has no effect on morphology or locomotive rate. Divalent cations are not required for adhesion, but external calcium is required for normal locomotion. In the presence of calcium, Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Whatever the extent of genomic integration that exists between the IRO and its host, it has not extended to the control of the mechanism of rDNA evolution. Therefore, the morphological (Martin 1987), antigenic (Villavedra et al 2005), and now genetic plasticity present in N. pemaquidensis may be considered the result of a complex adaptation of the amoeba and its endosymbiont to a wide range of life styles and environments.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the extent of genomic integration that exists between the IRO and its host, it has not extended to the control of the mechanism of rDNA evolution. Therefore, the morphological (Martin 1987), antigenic (Villavedra et al 2005), and now genetic plasticity present in N. pemaquidensis may be considered the result of a complex adaptation of the amoeba and its endosymbiont to a wide range of life styles and environments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reduced viability of gill amoebae and therapeutic benefit in soft fresh water was possibly, in part at least, attributed to a greatly reduced mucus viscosity. This effect on the mucous layer would result in the subsequent harmful exposure of amoebae to soft fresh water (Martin 1987; Powell & Clark 2003) and result in an increased sloughing of mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, only dissolved calcium was a predictor in the model for N. pemaquidensis survival in this study. Calcium ions play an important role in cell morphology and locomotion (Martin 1987) and may have been a limiting factor in this study. Ammonia did not significantly change the survival of N. pemaquidensis in the in vitro study, suggesting that any possible nutrient build‐up due to aquaculture (McGhie et al.…”
Section: Discussionmentioning
confidence: 99%
“…The chelating properties of DOC can also result in the depletion of other essential ions such as calcium and magnesium (Zhao, Jaiteh, Wang & Stevens 1999). Calcium is required for amoeboid movement (Jahn & Bovee 1969), including N. pemaquidensis (Martin 1987), while magnesium is involved in the synthesis of actin and actomyosin fibres and the activation of ATP (Perry 1967). Previous studies have shown that both calcium and magnesium ions are essential for the survival of N. pemaquidensis in both fresh (Powell & Clark 2003; Roberts & Powell 2003) and sea water (Green 2003).…”
Section: Introductionmentioning
confidence: 99%